Sub‐Ice Platelet Layer Physics: Insights From a Mushy‐Layer Sea Ice Model. Issue 6 (15th June 2021) - Wongpan, P.; Vancoppenolle, M.; Langhorne, P. J.; Smith, I. J.; Madec, G.; Gough, A. J.; Mahoney, A. R.; Haskell, T. G.
Abstract: The sub‐ice platelet layer (SIPL) is a highly porous, isothermal, friable layer of ice crystals and saltwater, that can develop to several meters in thickness under consolidated sea ice near Antarctic ice shelves. While the SIPL has been comprehensively described, details of its physics are rather poorly understood. In this contribution we describe the halo‐thermodynamic mechanisms driving the development and stability of the SIPL in mushy‐layer sea ice model simulations, forced by thermal atmospheric and oceanic conditions in McMurdo Sound, Ross Sea, Antarctica. The novelty of these simulations is that they predict a realistic model analogue for the SIPL. Two aspects of the model are essential: (a) a large initial brine fraction is imposed on newly forming ice, and (b) brine rejection via advective desalination. The SIPL appears once conductive heat fluxes become insufficient to remove latent heat required to freeze the highly porous new ice. Favorable conditions for SIPL formation include cold air, supercooled waters, and consolidated ice and snow that are thick enough to provide sufficient thermal insulation. Thermohaline properties resulting from large liquid fractions stabilize the SIPL, in particular a low thermal diffusivity. Intense convection within the isothermal SIPL generates the SIPL‐consolidated ice contrast without transporting heat. Using standard physical constants and free parameters, the model successfully predicts the SIPL and consolidated ice thicknesses at six locations. While most simulations were performed with 50 layers, an SIPL emerged with moderate accuracy in thickness for three layers proving a low‐cost representation of the SIPL in large‐scale climate models. Plain Language Summary: The sub‐ice platelet layer (SIPL) is a typical feature beneath sea ice near the Antarctic coast. The SIPL, made of ∼10 cm‐large ice crystals bathed in salt water, can be several meters thick and harbor exceptionally prolific micro‐algae. Much of coastal Antarctica is occupied by massive glaciers that float upon the ocean. We know that meltwater, released by glacial melting at depth, rises and refreezes on its ascent, sourcing ice to the SIPL. Yet many aspects of the growth and decay of an SIPL are poorly understood. Here, we present the first realistic simulations of the SIPL phenomenon near McMurdo Sound, Antarctica, based on a computer model encapsulating state‐of‐the‐art sea ice physics. The simulations inform us of features within the SIPL that are difficult to observe directly and help us understand why the SIPL is common, thick, and long‐lasting. In our simulations, the large volume of saltwater bathing the SIPL crystals buffers heat transfer and favors salt transfer, stabilizing the SIPL and generating a contrast with the consolidated sea ice above the SIPL. We also suggest a method of achieving an SIPL in climate models, which will help define its role in polar climate and ecology. Key Points: A realistic sub‐ice platelet layer (SIPL) emerges in a one‐dimensional thermodynamic sea ice model when suitably forced Key influences are heat loss to water column, thermal insulation by ice and snow, and brine convection between platelet crystals The SIPL is stabilized by its high liquid content and isothermal character